2016
DOI: 10.1161/atvbaha.115.306074
|View full text |Cite
|
Sign up to set email alerts
|

NG2 Proteoglycan Ablation Reduces Foam Cell Formation and Atherogenesis via Decreased Low-Density Lipoprotein Retention by Synthetic Smooth Muscle Cells

Abstract: Objectives Obesity and hyperlipidemia are critical risk factors for atherosclerosis. Since ablation of NG2 proteoglycan in mice leads to hyperlipidemia and obesity, we investigated the impact of NG2 ablation on atherosclerosis in ApoE null mice. Approach and Results Immunostaining indicates that NG2 expression in plaque, primarily by synthetic smooth muscle cells, increases during atherogenesis. NG2 ablation unexpectedly results in decreased (30%) plaque development, despite aggravated obesity and hyperlipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
0
7
1
1
Order By: Relevance
“…Abnormalities of the pituitary gland have not been described in global NG2 knockout mice (Chang et al 2012, She et al 2015. In marked contrast, here we show that targeted pRb inactivation in NG2-expressing cells results in striking pituitary tumor development in the anterior pituitary gland.…”
Section: Prb Inactivation In Ng2-expressing Cells Leads To Pit1-lineacontrasting
confidence: 68%
“…Abnormalities of the pituitary gland have not been described in global NG2 knockout mice (Chang et al 2012, She et al 2015. In marked contrast, here we show that targeted pRb inactivation in NG2-expressing cells results in striking pituitary tumor development in the anterior pituitary gland.…”
Section: Prb Inactivation In Ng2-expressing Cells Leads To Pit1-lineacontrasting
confidence: 68%
“…With the advent of extraction techniques, which preserved the protein moieties of the PGs and provided a means to recover intact PGs from vascular lesions [64-67], together with the use of antibodies, which recognized different core proteins, it became clear that the different GAGs within the lesions were attached to specific core proteins. Thus, it is now recognized that the bulk of the CS chains present in atherosclerotic lesions are present as the PG versican, although other CS-containing PGs such as aggrecan [68, 69] and NG2 [70] have been found as well! The DS chains within blood vessels and atherosclerotic lesions are distributed between two highly homologous core proteins of the small leucine rich repeat (SLRP) family and form the PGs decorin and biglycan while KS is also present in the SLRP family as fibromodulin and lumican [6, 7].…”
Section: Proteoglycans In Cardiovascular Diseasementioning
confidence: 99%
“…16 She et al reported that the conversion of SMCs to foam cells may be accelerated by expression of neural/glial antigen-2 (NG2) proteoglycan on the surface of synthetic SMCs. 66 Despite the fact that ablation of NG2 proteoglycan in mice leads to hyperlipidemia and obesity, both risk factors for the progression of atherosclerosis, when tested on an ApoE-null background loss of NG2 expression unexpectedly results in reduced plaque development. 66 These results suggest that local acquisition of a macrophage like proinflammatory phenotype by plaque SMCs plays a more predominant role in plaque progression than systemic hyperlipidemia or obesity.…”
Section: Vascular Smcs Inflammation and Atherosclerosismentioning
confidence: 99%
“…66 Despite the fact that ablation of NG2 proteoglycan in mice leads to hyperlipidemia and obesity, both risk factors for the progression of atherosclerosis, when tested on an ApoE-null background loss of NG2 expression unexpectedly results in reduced plaque development. 66 These results suggest that local acquisition of a macrophage like proinflammatory phenotype by plaque SMCs plays a more predominant role in plaque progression than systemic hyperlipidemia or obesity. Finally, an emphasis on the role of local factors in the control of macrophage-like phenotype transition of plaque SMCs emphasizes the role of SMC-derived ECM proteins in plaque progression.…”
Section: Vascular Smcs Inflammation and Atherosclerosismentioning
confidence: 99%